Modelling Plantar Pressure in a Smart Wearable Insole System Using Piezoresistive Sensors - Sekhah Ulyana; Husneni Mukhtar; Willy Anugrah Cahyadi; Nigel Bryan Tang (Ikatan Ahli Informatika Indonesia (IAII), 2026)
Biomechanical analysis plays a crucial role in evaluating movement patterns and pressure distribution. It enables early detection of abnormal gait and posture that may lead to long-term musculoskeletal problems. By identifying pressure imbalances, biomechanical assessment supports injury prevention, rehabilitation monitoring, and personalised orthotic design. However, conventional tools are often bulky and expensive, limiting accessibility. This study introduces an insole system that integrates piezoresistive sensors with Radial Basis Function (RBF) interpolation to provide cost-effective, real-time visualisation of plantar pressure. Tests involving five subjects, conducted during standing, stair climbing, and walking, revealed distinct load patterns with a strong correlation to reference data (R² = 0.925). The static standing test demonstrated balanced pressure and an average MAPE of 24.9%, while the walking cycle exhibited consistent heel-to-toe transitions and proper weight transfer. Operating at a 10 Hz sampling rate, the wearable insole accurately quantified plantar pressure variations, demonstrating its potential for real-time gait assessment and rehabilitation monitoring.